УЛС ТӨРИЙН ОРЧИН ДАХЬ ИМИЖМЕЙКЕРИЙН ҮҮРЭГ - У.Батцэрэн (Politology, 2023)
That’s very important to have an image in the political arena. Services should be organized by professionals and shouldn’t be inexplicit or blind in politics and society. Through all stages of elections high level image-makers use their election methodology and experience to help candidates in all aspects of the campaign. Who is an image - maker?, his purpose and goal, become as a political expert, information printing, conaltation.